2007
DOI: 10.1016/j.acn.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Army research needs for automated neuropsychological tests: Monitoring soldier health and performance status☆

Abstract: Information on the mental status of soldiers operating at the limits of human tolerance will be vital to their management in future deployments; it may also allow earlier intervention for conditions such as undiagnosed Gulf War illnesses and Parkinson's Disease. The Army needs a parsimonious set of neuropsychological tests that reliably identify subtle changes for: (1) early detection of individual health and military performance impairments and (2) management of occupational and deployment health risks. Testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 33 publications
(29 reference statements)
1
30
0
Order By: Relevance
“…On the other hand, military personnels practice lifestyle habits similar to the general population which may predispose them to CVD, such as smoking, alcohol intake, and sedentary lifestyle habits. Recently, studies have demonstrated a trend toward increasing hypertensive disease among KDF consistent with other military personnel [1214] globally. The causation may be multifactorial including occupation-related stress, a potentially important cardiovascular risk factor [1517].…”
Section: Introductionsupporting
confidence: 58%
“…On the other hand, military personnels practice lifestyle habits similar to the general population which may predispose them to CVD, such as smoking, alcohol intake, and sedentary lifestyle habits. Recently, studies have demonstrated a trend toward increasing hypertensive disease among KDF consistent with other military personnel [1214] globally. The causation may be multifactorial including occupation-related stress, a potentially important cardiovascular risk factor [1517].…”
Section: Introductionsupporting
confidence: 58%
“…Starting forceful military service at the age of 18 years old is stressful for adolescent soldiers, and there is a comprehensive report on the record of mental illnesses in terms of their diagnosis, treatment, and symptomatology at the same time (2)(3)(4). The slur of mental disease disheartens young soldiers from reporting signs of disease and from getting help (5).…”
Section: Introductionmentioning
confidence: 99%
“…The second stage is becoming adjusted to the contradictory conditions of combat or the risk of war (2). Reportedly, people who are emotionally competent facilitate confronting challenges expanding their mental healthfamily illness were found to be associated with emotional reactions (9).…”
Section: Introductionmentioning
confidence: 99%
“…The management of fatigue is an important issue in society and there is increasing interest in the development of objective non-invasive systems that can be used to assist the identification and management of fatigue in both health and workplace settings (e.g., military operations, extended hours performed by medical workers) (Gaba and Howard, 2002;Maruff et al, 2005;Friedl et al, 2007). Assessment of the acoustic properties of speech provides reliable insight into damage and injury to the central nervous system (CNS), as speech often changes as a function of variety of insults, including neuromuscular degenerative disease (Josephs et al, 2006;Folker et al, 2010) or brain injury (Ziegler et al, 1993).…”
Section: Introductionmentioning
confidence: 99%